The Effect of Liquidity and Leverage on Share Prices in Metal Subsector Manufacturing Companies Listed on BEI Th 2018-2021 - Frisca Widya Diningsih; Teti Chandrayanti; Delori Nancy Meyla (Jurnal Riset Manajemen, 2025)
The average condition of share prices in metal sub-sector manufacturing companies in 2018 - 2021 was fluctuating, a significant decline in share prices occurred in 2021 with a nominal value of 568.19. The decline in shares in the capital market was marked by a decline in investor interest in several sectors and also a decline in the manufacturing index which resulted in a weakening of the national economy. The aim of the research is to determine the effect of liquidity and leverage on share prices in metal sub-sector manufacturing companies listed on the IDX 2018-2021. The data collection method is Library Research. The type and source of data is secondary data. Population is a whole or set of similar objects. The population in this study were 17 metal sub-sector manufacturing companies listed on the IDX 2018-2021. The sample used in this research was 11 companies using company financial reports for the period 2018 to 2021. So the total sample in this research was 11 companies x 4 periods = 44 financial reports.  The analytical method used is multiple linear regression analysis, coefficient of determination and hypothesis testing t and F. The results of the research found: (1) liquidity has a significant positive effect on share prices in metal sub-sector manufacturing companies listed on the IDX 2018-2021. (2) Leverage has a positive effect on share prices in metal sub-sector manufacturing companies listed on the IDX 2018-2021, (3) together the liquidity and leverage variables have an insignificant effect on share prices in metal sub-sector manufacturing companies listed on the BEI 2018-2021.